STRUCTURAL REVIEW OF HORIZONTALLY IRREGULAR BUILDINGS USING PUSHOVER AND TIME HISTORY ANALYSIS - RM, Redha Arima; Zainal, Edwina; Khaidir, Indra (SIGMA TEKNIKA, 2025)
Padang City, the capital of West Sumatra, is one of the earthquake-prone regions in Indonesia due to its location between two of the world's active tectonic plates. In earthquake-resistant buildings, the geometry of the structural layout plays a crucial role in how the building responds to seismic forces. Regular, simple, and symmetrical structures tend to perform better during earthquakes compared to irregular ones. The purpose of the research is to evaluate the building's structural capacity under seismic loads, including identifying potential failure mechanisms. The analysis was carried out using the nonlinear pushover method with ETABS software to perform a performance-based design evaluation. The output parameters and structural performance assessment were based on the standards of the Applied Technology Council ATC-40, FEMA 356, and FEMA 440 guidelines. Based on the results, the maximum shear force the structure can withstand is 18,344.6041 kN with a displacement of 291.435 mm under Push-X, and 18,611.7226 kN with a displacement of 190.459 mm under Push-Y. These displacement values remain below the allowable limit of 2% of the building height (H), which is 442 mm. The analysis also revealed a maximum total drift of 0.013 in the X-direction and 0.010 in the Y-direction, while the maximum inelastic drift was 0.011 in the X-direction and 0.006 in the Y-direction. According to Drift Limitation performance parameters, the structure falls under the Damage Control (DC) performance level. Further nonlinear Time History analysis using different earthquake records showed the following maximum drift values Northridge 1994 Earthquake 2.45%, Kobe 1995 Earthquake 7.598%, Chichi Earthquake 5.757%, Scaled Padang Earthquake Record 2.174%. These results demonstrate how different earthquake events affect the performance of an irregular building and highlight the importance of conducting detailed seismic evaluations in earthquake-prone regions such as Padang.